PERAN POLRESTABES MEDAN DALAM PEMBERANTASAN NARKOTIKA DIHUBUNGKAN DENGAN TINDAK PIDANA PENCUCIAN UANG - Wira Prayatna; Alvi Syahrin; Bismar Nasution Nasution; Mahmud Mulyadi (Universitas Sumatera Utara, 2017)
ABSTRACT Efforts to combat narcotics connected with money laundering committed Polrestabes Medan, is specifically addressed by the Investigation Unit of Drug Polrestabes Medan (Sat Res Drugs Polrestabes Terrain) which is the main executor drugs in order P4GN, Polrestabes Medan in carrying out anti-narcotics linked to money laundering, of course, there are many barriers, both technically and legally. Polrestabes field must also make efforts to overcome the obstacles to the eradication of drugs associated with money laundering, both efforts internally and externally efforts. This brings to Basic settings need to be assessed on the police authorities in combating narcotic crime related to money laundering. Terrain Polrestabes role in the eradication of narcotics-related money laundering. Problematic Polrestabes field in the eradication of narcotics-related money laundering. Keywords: Polrestabes Medan, Narcotics and Money Laundering